STRATEGI PUBLIC RELATION DALAM PELAYANAN INFORMASI (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2005)
AbstractEssential of Public Relations activity is communication, both internal and external organization or instutions.  Principle of effective communication is communicator must oriented to communicant.  Whereas, communicant or target audience of Public Relations has odifference characteristic and self interest to organization.  That difference which cause Public Relations approach is difference too.  So, actually we neeed a strategy for information service is effectively. Strategy of Public Relations is the best alternative is choosen for achieving the goal of Public Relation plan. Public Relations objective is establish and develoving favorable image for organization or institution.  For that, activity of Public Relations is directed effort perception of stakeholders, have root them attiude.  If the process making is success, so found favorable opinion, take turn will establish favorable image. In making satrategy in information service, there are four important elements must be attentioned, that is ; the credibility of Public Relations Officer ( PRO ), internal coordination in organization or institution, favorable relation between Public Relations Officer with source of information, and package of massage oriented to target audience. Keywords: Strategic public relations, pelayanan informasi